Quantitative analysis on the microstructure of molten binary KF‐AlF3 system by in situ Raman spectroscopy assisted with first principles method. (7th November 2019) - Ma, Nan; You, Jinglin; Lu, Liming; Xie, Yingfang; Wan, Songming
Abstract: In order to help predict the properties of molten salts electrolytes and aluminium brazing flux used in the Hall–Héroult process and in aluminium brazing, the microstructure of binary KF‐AlF3 system from 298 K to its molten states was explored by in situ high‐temperature Raman spectroscopy in argon atmosphere. Comparing with experimental Raman spectra in molten system, quantum chemistry ab initio simulations were used to calculate the symmetric stretching vibrational modes of probable clusters in the melts. The molten KF‐AlF3 system was found to comprise monomer [AlF6 ] 3−, [AlF5 ] 2−, [AlF4 ] −, and dimer [Al2 F7 ] − clusters. With the increase of KF content in the melts, the major species changes from [AlF4 ] − tetrahedra to [AlF6 ] 3− octahedra. From the deconvoluted measured Raman spectra, the mole fractions of varied clusters in the system were also calculated. As the KF:AlF3 ratio was increased from 1 to 3, the content of [AlF6 ] 3− in the melt increased from 22.30 to 98.83 mol%, whereas the [AlF4 ] − content decreased from 68.92 to 0.33 mol%. [AlF5 ] 2− and [Al2 F7 ] − clusters were also found in small amounts in the melts. Abstract : Qualitative and quantitative analysis of four clusters in molten binary KF‐AlF3 system were investigated by in situ Raman spectroscopy and first principles method.